Drug Titration Process Control and Identification System Using IoT-Based RGB Sensors - Jayati, Ari Endang; Wibowo, Fatmawati; Erlinasari, Erlinasari (Journal of Electrical Engineering and Computer (JEECOM), 2026)
The process of determining the levels of drug raw materials using the titration method in pharmaceutical laboratories is generally still carried out manually, potentially causing inaccuracy in determining the titration endpoint. This study aims to design and implement an automatic drug titration control and identification system using an Internet of Things (IoT)-based RGB color sensor. The system is controlled by a built-in ATmega 2560 WiFi microcontroller integrated with a dosing pump as an actuator for adding titrant and a DC motor as a solution stirrer. The RGB sensor is used to detect color changes in the solution until it reaches orange as an indicator of the titration endpoint. The results of the titration process, in the form of process time and titrant volume, are sent in real-time via WhatsApp notifications. Tests were conducted on several drug raw materials, namely stearic acid, boric acid, and citric acid. The test results showed that the system was able to work as designed with titration results close to the manual method, with the highest accuracy level reaching 98.7%. This system is expected to improve the efficiency and consistency of the titration process in pharmaceutical laboratories.